Interaction patterns on body size and health on Instagram and associated factors in nutrition students: an exploratory study - Alves FLAUZINO, Pabyle; Ferreira CARIOCA, Antonio Augusto (Revista de Nutrição, 2022)
Objective To identify interaction patterns on body size and health on Instagram and associated factors in nutrition students. Methods A total of 406 students (78% female) were included in this cross-sectional study. Instagram sociodemographic, academic and interaction data (Instagram time of use, exposure frequency to contents on body size and health, Instagram as a source of information and number of followers) were collected using a self-administered virtual questionnaire. A factor analysis by main component was used to derive the interaction patterns of Instagram as well as regression analyses to test the association of the patterns with the sociodemographic and academic factors. Results Three interaction patterns were observed on body size and health, named: “Fitness Pattern”; “Body Positivity Pattern” and “High Engagement Pattern”. Private Institutions’ Students who are on or have been on a diet and studying in the first semesters were associated with the “Fitness Pattern” (p<0.05). Female students, from public institutions, who changed their weight during the course and whose family’s head had higher education, were associated with the “Body Positivity Pattern” (p<0.05). Female students, younger and on a diet, were associated with the “High engagement Pattern” (p<0.05). Conclusion Gender, type of educational institution and diet practice of nutrition students are the factors that are most associatedwith different patterns of interaction on body size and health on Instagram.